HUBUNGAN GREEN MARKETING TERHADAP PILIHAN KONSUMEN ( Studi Kasus Pada The Body Shop Manado ) - Magdalena E. Angeline; Charles R. Ngangi; Esry O.H. Laoh; Mex L. Sondakh (Universitas Sam Ratulangi, 2015)
ABSTRACT Magdalena Elisabeth Angeline. Relationship Green Marketing with consument choice ( Case study on the body shop manado ) under the guidance of Charles R. Ngangi, as Chairman , Esry H. Laoh and, Mex L Sondakh,MSi as Members. The study aims to determine the relationship of green marketing with consumers choice in the Body Shop Manado. Data collection is done for 4 months from September 2014 until January 2015. The data that used in this study are primary data and secondary data. Primary data obtained by distributing questionairs to consumers The Body Shop Manado as well as interviews with the parties Manado The Body Shop. Secondary data obtained from the literature related to green marketing. The results of this study indicate that there is a relationship between green marketing with consumer choice. Where by pursuing a strategy of green marketing on the business activities carried out by The Bod y Shop Manado like her doing things green product, green promotion, green price, and green place can give effect to the increase. Of the increase in positive perception of costumers on the importance of using green products lead to changes in their behaviour. It can be proved on the second enhacement indicator that as many as 79,25% of respondents are willing to build more for environmentally friendly green products in terms of promotions, The Body Shop Manado already well positioned company, as evidenced by the increased of the 15th that as many as 86,25% respondents believe that they liked the promotion of The Body Shop Manado who use public relations program because it is considered more exclusive that the other brands. The main implications is The Body Shop Manado should pay attention to the quality aspect to offset the high prices and women as it‟s main market. Keyword : green marketing, and consumers choice